Youth Adjudicated for Sex Offenses, Followed into Adulthood, and Found on a State Sex Offender Registry. Issue 10 (26th November 2022) - Lee Rasmussen, Lucinda A.
ABSTRACT: Youth who were adjudicated for sex offenses ( N = 145) and placed in a secure custody residential facility were followed for 15.76 years into adulthood (mean follow-up = 12.68 years, SD = 1.71). Subjects were assessed by two contemporary risk assessment tools, JSORRAT-II, an actuarial tool, and the risk level tool, MEGA ♪ . A portion of the sample ( n = 129) were previously followed for 6 years (mean follow-up = 15.6 months, SD = 9.78). Sexual recidivism was 17.4%, defined by the program's parameters (i.e., a new sexual behavior rising to the level that the youth's probation officer was contacted). Unique to the study was the selected predictive variable, placement on a state sex offender registry, designed to identify those individuals who recidivated with a conviction for a serious sex offense. Sexual recidivism was 6.2%, according to a search of the California Megan's Law Sex Offender Registry Website. Implications of examining sexual recidivism through using sex offender registries are discussed, as well as the potential utility of risk level tools in identifying youth who are at risk for seriously harmful sexually abusive behavior.